O poema O Guesa, de Sousândrade, à luz da hermenêutica de Paul Ricoeur - Oliveira, Rita de Cássia (2009)
The present philosophical work bears the title The O Guesa poem by Sousândrade, in light of Paul Ricoeur s hermeneutics and intends to be an interpretation which has as paradigm the Paul Ricoeur s Phenomenological Hermeutics with respect to showing the meaning of the present existence in the symbolism of poetic foundation. I thematize the question of poetic language in its narrative aspect in the O Guesa poem and its correlation with the pertinent literature and philosophy to highlight the metaphoricity as a poetic language condition because it is constituted in a differentiated mode of thinking the world. Ricoeur turns to Aristotle Poetics and Rhetoric works as a starting point of his investigation on the significance of metaphor power when permitting that something is said indirectly by the joining of disconnected images having, nevertheless, an enclosed truth. I follow Ricoeur s same procedure in La métaphore vive, and look upon Aristotle for an understanding about the theory of metaphor in adequation to the analysis of the O Guesa poem. The development of the study reaches a correlation between the hermeneutic and the theory of narativity as to the interpretation of the act of narrating as an origin of rationality that tells actions and events according to an ordering which is characterized as the machination plot. Ricoeur s books that sustain this survey are, chiefly, La mémoire, l histoire, l oubli, Du texte à action and Temps et récit which reveal Ricoeur s reflection on the narrative identity as resulting from the interweaving of history with fiction. The narrative identity, a theme developed in Soi-même comme Un Autre, requires that Ricoeur imagine the subject in his interpersonal and institutional reflexives, bringing forth ethics and moral as indispensable knowledge for a philosophy which recognizes literature as being a vast laboratory of human experience